CO2 capture from indoor air for human comfort and sequestration or reuse: a promising step toward sustainable CO2 removal - Maity, Krishnendu; Bhadirke, Shreyash D.; Wijewardane, Samantha; Goswami, D. Yogi (Frontiers in Nanotechnology, 2025)
Concentration of CO2 in an indoor environment can be four to five times higher than the outdoor air. This higher indoor concentration of CO2 reduces the work efficiency of individuals working indoors and negatively impacts human health. However, the elevated concentration also makes it easier to capture CO2 from indoor air. This study examines the performance of monoethanolamine (MEA) and L-arginine (Arg) solutions for indoor carbon dioxide (CO2) capture through experimental screening. Key parameters evaluated include CO2 absorption and desorption capacity, absorption kinetics, and the impact on relative humidity (RH) and total volatile organic compound (TVOC) concentrations. Two solvent formulations were employed in this study: one utilizing pure water as the solvent and the other incorporating a water-glycol mixture. The aqueous Arg solution demonstrated minimal to no detectable increase in VOC levels and exhibited lower evaporation rates than the benchmark aqueous MEA solution. Microwave (MW) heating was utilized to facilitate rapid CO2 desorption from saturated solutions. The regeneration efficiency, solvent loss, and energy consumption were found to be dependent on the MW desorption time. Optimizing the desorption resulted in faster and almost complete regeneration, minimized solvent loss, and reduced overall energy consumption. The incorporation of glycol minimized evaporation during absorption, decreased the likelihood of complete drying during desorption, and improved solution regeneration. Cyclic absorption-desorption experiments were conducted to evaluate the long-term stability and kinetic performance of the solutions. While the aqueous MEA solution experienced significantly larger declines of 54.3% in CO2 absorption capacity and 34.24% in absorption kinetics, the water-PG-based Arg solution demonstrated promising performance, with a smaller reduction of 31.24% in CO2 absorption and a 2.13% decrease in kinetics after ten cycles. Additionally, the water-PG-based Arg solution resulted in lower volatile organic compound (VOC) levels and provided more effective control over relative humidity. These findings underscore the potential of the water-PG-based Arg solution for cyclic CO2 absorption and microwave-assisted regeneration processes.